Effect of second phase particles topology on the onset temperature of abnormal grain growth in Fe - 3%Si steels - Stoyka, V.; Kovac, F.; Sidor, Y. (Metalurgija, 2008)
The relations between regimes of dynamic annealing, state of secondary particles system and the onset temperature of abnormal grain growth are investigated. Two distinguish types of Fe-3%Si grain-oriented steels, after one and two stage cold rolling, were studied. The second phase particles remain unaffected in first type of steel during the heat treatment. Vice versa, the increased density of second phases was observed after annealing in the second type of the investigated materials. It is shown that start/onset of abnormal grain growth strongly depends on both volume fraction of second phase particles and annealing temperature. Texture and magnetic properties of the investigated samples are investigated within the current study.